Educator preparation: a multi-discipline analysis of standards to promote critical thinking. (19th May 2023) - Carter, Richard Allen; Zhang, Ling; Hunt, Tiffany L.; Bloom, Lisa; Wilder, Tahnee L.; Yang, Sohyun; Parsons, Christine
ABSTRACT: Teacher education standards are designed to guide the preparation of pre-service teachers to acquire knowledge and develop skills required for delivering high-quality educational experiences to all learners. Analysing how critical thinking (CT) is positioned in educator preparation standards is an initial step towards understanding the conceptualisation and operationalisation of CT in teacher education. In this study, a team of researchers analysed U.S. educator preparation standards across multiple disciplines and learner populations through a crosswalk standards database for the presence of CT, gaps in the standards, and relation among standards. Results indicate that most CT-related standards focus on preparing teachers to perform strategies that promote CT for students. Less prevalent, or missing, are standards that prepare teachers with essential knowledge of the role of CT in the classroom, using assessment to monitor CT, or the role of planning to provide CT learning experiences. Implications for these gaps are discussed.